Transformation of local knowledge of Lubuk Larangan toward fishing tourism - Mangunjaya, Fachruddin Majeri; Bahagia, Bahagia; Praharawati, Gugah; Yarni, Yarni; Aadrean, Aadrean; Kurniawan, Ritno (Program Pascasarjana Universitas Negeri Yogyakarta, 2021)
This research aims to investigate the transformation of local knowledge of Lubuk Larangan toward tourism. The research method uses an ethnographic qualitative approach. This method is implemented because this research has a connection to customary societies. To gather data was used as an in-depth interview. Samples are selected through the purposive technique. The result is probed meticulously through the triangulation technique and triangulation sources. The result shows that customary community conferences locally impact the conservation of nature and fish in Lubuk Larangan. Deliberations determine the time of harvesting fish in the forbidden pit area and determine the area used as a prohibited area. There were 10 ninik mamak in attendance and one ninik mamak as the leader of the ten ninik mamak. Another finding is that democratic principles such as decisions on the basis of togetherness for the common interest are applied to the forbidden area. The last finding is that there is a transformation of social and cultural values in the Lubuk Larangan area. Customary rules are very strict, but interfering with the younger generation to overhaul traditional rules makes the traditional leaders adapt to the wishes of the younger generation to serve as fishing tourism areas. Several considerations were found at the time the Lubuk Larangan area had not been changed. The rules were detrimental because when the event opened the Lubuk Prohibition area, it resulted in the exhaustion of fish, and profits were only obtained 30 million in 3 years. When it has been converted into fishing tourism, it impacts increasing profits to reach 30 million in a month. Plus, the fish will not become extinct because the fish caught when fishing will be released again. People even get the opportunity to offer tent rental services, sell food and drinks, become tour guides, and offer to lodge for tourists who come.